2002
DOI: 10.1007/pl00012523
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin D3 and p53 mediate sulforaphane-induced cell cycle delay and apoptosis in non-transformed human T lymphocytes

Abstract: Despite experimental evidence that sulforaphane can exert chemopreventive effects, whether these effects are specific for neoplastic cells is not known. Following our previous demonstration that sulforaphane induces cell cycle arrest and apoptosis in human T lymphoblastoid Jurkat leukemia cells and increases p53 and bax protein expression, we tested sulforaphane on non-transformed phytohemagglutinin-stimulated human lymphocytes. Here, we demonstrate that sulforaphane arrested cell cycle progression in G, phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 32 publications
(29 reference statements)
1
22
0
Order By: Relevance
“…One possibility involves the inhibition of cell proliferation. It was previously demonstrated that the treatment of human lymphocytes with 3, 10 and 30 mM sulforaphane induces a block in cell-cycle progression through an accumulation of cells in G 1 phase [Fimognari et al, 2002b]. We postulate that treatment with sulforaphane delays cell-cycle progression, thus reducing the number of cells reaching M phase, on which VIN acts.…”
Section: Discussionmentioning
confidence: 93%
“…One possibility involves the inhibition of cell proliferation. It was previously demonstrated that the treatment of human lymphocytes with 3, 10 and 30 mM sulforaphane induces a block in cell-cycle progression through an accumulation of cells in G 1 phase [Fimognari et al, 2002b]. We postulate that treatment with sulforaphane delays cell-cycle progression, thus reducing the number of cells reaching M phase, on which VIN acts.…”
Section: Discussionmentioning
confidence: 93%
“…An example of such simultaneous membrane signals might be the induction of Fas receptor clustering in Jurkat cells (2). By contrast, the divergent effect of impairing cyclin and cdk activity that leads to cell cycle arrest in A549 or apoptosis in Jurkat cells, may also reflect the downstream crosstalk mechanisms (2,3,(21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of p53 in SF-mediated apoptosis is not clear. Reports from Fimognari and colleagues suggest that SF treatment increased the expression of p53 protein in non-transformed human T lymphocytes [137], and this increase was associated with a significant increase in the protein levels of Bax and a slight decrease in Bcl-2 measured in T cell leukaemia cells [138]. In contrast, levels of p53 and Bcl-2 remained unchanged in response to SF treatment in HT29 cells [110].…”
Section: The Role Of Bcl-2 Family In Sf-mediated Apoptosismentioning
confidence: 97%